Pengaruh Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai PT. Himpun Jaya Permata - Rina Loliyana; Rini Loliyana (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research was conducted to find out how much influence human resource development has on employee performance at PT. Himpun Jaya Permata. The research method used in this research uses quantitative research methods. In validity testing, it is known that the value of r calculated is greater than r table, namely r table 0.339 and r calculated 0.783 so it can be said that the results of both are valid. From the results of the reliability test, the human resource development variable is 0.866 and the employee performance variable is 0.815. Based on these results, in this reliability test, each variable is said to be reliable because it exceeds the Cronbach Alpha value, namely 0.60. From the results of the simple linear regression analysis, it is known that the coefficient is constant. (a) is 15,140 and the regression direction coefficient (b) is 1.078 and the significance value obtained from the table above is 0.000 < 0.05 so it can be concluded that the Human Resource Development variable (X) influences the Employee Performance variable and the magnitude of the correlation value (R ) is 0.844 and the Coefficient of Determination (R Squere) is 0.713, which means that the influence of the independent variable on the dependent variable is 71.3%.